The Palgrave Handbook of Family Policy 2020
DOI: 10.1007/978-3-030-54618-2_21
|View full text |Cite
|
Sign up to set email alerts
|

Company-Level Family Policies: Who Has Access to It and What Are Some of Its Outcomes?

Abstract: Despite the increase in the number of studies that examine the cross-national variation in the policy configuration that allow a better work–family integration, very few look beyond the national levels. It is also crucial to examine occupational level welfare since companies may restrict or expand the existing national-level regulations, defining the “final availability” workers actually have toward various arrangements. In addition, companies may provide various additional arrangements through occupational po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 120 publications
0
10
0
1
Order By: Relevance
“…India, Netherlands and Spain contributed one paper each. A range of family-friendly policies and practices documented by researchers in their research papers included flexible working options (such as flextime, compressed workweek, work from home/telework, job sharing and part-time), organizational support for dependent care (such as health and medical facilities), child care assistance measures (such as onsite childcare/cr eches, kindergarten and childcare allowance), leave policy (such as leave for maternity/paternity, adoption, casual, compassionate, education, sabbaticals and training), informational services like eldercare assistance and support for miscellaneous activities such as laundry services (Beauregard and Henry, 2009;Chung, 2020;Cieri et al, 2005;Darcy et al, 2012;Lai-ching and Kam-wah, 2012;McDonald et al, 2005;Smith and Gardner, 2007). The work culture of a country, to a larger extent, determines the company's provision for WLBPs (Chung, 2020).…”
Section: Bibliographic Coupling Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…India, Netherlands and Spain contributed one paper each. A range of family-friendly policies and practices documented by researchers in their research papers included flexible working options (such as flextime, compressed workweek, work from home/telework, job sharing and part-time), organizational support for dependent care (such as health and medical facilities), child care assistance measures (such as onsite childcare/cr eches, kindergarten and childcare allowance), leave policy (such as leave for maternity/paternity, adoption, casual, compassionate, education, sabbaticals and training), informational services like eldercare assistance and support for miscellaneous activities such as laundry services (Beauregard and Henry, 2009;Chung, 2020;Cieri et al, 2005;Darcy et al, 2012;Lai-ching and Kam-wah, 2012;McDonald et al, 2005;Smith and Gardner, 2007). The work culture of a country, to a larger extent, determines the company's provision for WLBPs (Chung, 2020).…”
Section: Bibliographic Coupling Analysismentioning
confidence: 99%
“…The detailed examination of research articles in this cluster suggests that there lies a gap between the availability and usage of multiple WLBPs by employees, in particular, due to lack of organizational support for the uptake of these policies by employees, the gendered nature of policy usage and perception of negative career consequences by employees (Dulk and Ruijter, 2008;McDonald et al, 2005). Further, Chung (2020) argues that the individuallevel determinants of WLB policy specifically include FWA, as such arrangements are viewed as a component of high-performance strategy, employed not only to suit the needs of employees but also to improve the company's performance outcomes. Research studies by Brough et al (2008) and Zheng et al (2015) suggest that providing WLBPs not only helps IJSSP 42,11/12 employees to enhance their well-being but also facilitates greater fertility along with increased labor employment.…”
Section: Bibliographic Coupling Analysismentioning
confidence: 99%
“…Flexibility in the workplace is broadly desired by employees (Chung, 2020a;Jacobs & Gerson, 2004): In a 2018 study, 95 percent of women and 97 percent of men reported a need for work flexibility (Dean & Auerbach, 2018). However, only 29 percent of wage and salary workers have access to flexplace and 57 percent have access to flextime (U.S. Bureau of Labor Statistics, 2019).…”
Section: Defining Workplace Flexibility Policiesmentioning
confidence: 99%
“…Flexibility policies are considered key family-friendly initiatives, as they can help families balance competing demands from work and family responsibilities (Chung, 2020a;Gerstel & Clawson, 2018;Jacobs & Gerson, 2004). For example, parents may be able to arrange their schedules around family responsibilities, such as picking up children or having dinner with the family; and working from home may eliminate time-intensive commutes.…”
Section: Defining Workplace Flexibility Policiesmentioning
confidence: 99%
See 1 more Smart Citation